 |
cos(A/2) = -cos(A - B) cos(A/2) + cos(A - B) = 0 2cos((3A/2 - B)/2)cos((-A/2 + B)/2) = 0
cos((3A/2 - B)/2) = 0 (3A/2 - B)/2 = 2n(pi) + pi/2 or (3A/2 - B)/2 = 2n(pi) - pi/2 3A/2 - B = (4n + 1)pi or 3A/2 - B = (4n - 1)pi 3A/2 = (4n + 1)pi + B or 3A/2 = (4n - 1)pi + B A = 2(4n + 1)pi/3 + 2B/3 or 3A/2 = 2(4n - 1)pi/3 + 2B/3 so, x = sin(2(4n + 1)pi/3 + 2B/3) or x = sin(2(4n - 1)pi/3 + 2B/3) so, x = sin(2B/3) or x = sin(2(pi + B)/3) or x = sin(2(2pi + B)/3) or, x = 0.4160 or x = 0.5796 or x = -0.9955 >>> เช็คคำตอบแล้วใช้ไม่ได้ทุกค่า
cos((-A/2 + B)/2) = 0 (-A/2 + B)/2 = 2n(pi) + pi/2 or (-A/2 + B)/2 = 2n(pi) - pi/2 -A/2 + B = (4n + 1)pi or -A/2 + B = (4n - 1)pi A/2 = B - (4n + 1)pi or A/2 = B - (4n - 1)pi A = 2B - 2(4n + 1)pi or A = 2B - 2(4n - 1)pi x = sin(2B - 2(4n + 1)pi) = sin(2B) or x = sin(2B - 2(4n - 1)pi) = sin(2B) so, x = sin(2B) = 24/25 ###
==========
เดี๋ยวจะมาโพสต์วิธีที่สวยกว่านี้ครับ
แก้ไขเมื่อ 19 พ.ย. 54 19:35:22
แก้ไขเมื่อ 19 พ.ย. 54 15:03:10
จากคุณ |
:
TIYHz
|
เขียนเมื่อ |
:
19 พ.ย. 54 13:31:18
|
|
|
|
 |